O paradoxo dos agravos relacionados ao consumo de álcool e saúde bucal - Oliveira, Leandro Machado (2024)
Evidence consistently indicates that individuals in lower socioeconomic positions (SEP) are disproportionately affected by alcohol-related harms compared to those in higher SEP groups, even when they report similar or lower average alcohol consumption levels. Although there is robust evidence that lower SEP individuals experience poorer oral health and that alcohol consumption is a contributing factor to oral diseases, this paradoxical phenomenon remains unexplored in the context of oral health conditions. Understanding this relationship may provide a unique opportunity to develop public policies that address shared risk factors across multiple chronic diseases while considering social determinants of health. This thesis aimed to investigate the occurrence and impact of the alcohol-related health paradox (AHP) on adult oral health through seven outlined studies. The first study, utilizing data from the 2019 National Health Survey (PNS-2019), confirmed the AHP in Brazil, revealing that those in disadvantaged positions were 103% more likely to experience alcohol-related consequences than their higher SEP counterparts. Moreover, the socioeconomic gradient widened with increased average consumption volume and patterns. The second study, a systematic review (SR) of previously published SRs and prospective longitudinal studies, showed that evidence on the association between alcohol and periodontitis carries a high risk of bias. Only men with high alcohol consumption (HD) in socioeconomically disadvantaged contexts showed an elevated risk for periodontitis, with low certainty of evidence. The third and fourth studies, using data from the first wave of the Brazilian Longitudinal Study of Aging (ELSI-Brazil-1), demonstrated through effect modification analyses that HD was associated with higher magnitudes of nonfunctional dentition (NFD) and poorer oral health-related quality of life in lower SEP individuals, while higher SEP individuals showed the opposite effects. The fifth and sixth studies, drawing on data from ELSI-Brazil-1 and the 2011-2012 and 2013-2014 cycles of the National Health and Nutrition Examination Survey, explored mechanisms linking SEP and HD to NFD and periodontitis through a counterfactual approach called four-way decomposition. The findings suggest that differential susceptibility mechanisms connect SEP and HD to these oral health issues, indicating that SEP and HD interaction significantly contributes to oral health inequities. Finally, the seventh study, using PNS-2019 data, assessed the interaction effects of SEP and average alcohol consumption on NFD prevalence and poor self-perceived oral health. The findings confirmed the AHP, showing that moderate alcohol consumption was associated with higher prevalence rates of oral health problems among men and women with lower SEP, while negative associations were identified in those with higher SEP. In conclusion, the studies indicate that the AHP likely occurs within oral health outcomes.